Current topics in physics : in honor of Sir Roger J. Elliott - Barrio, R. A. (Rafael A.); Kaski, K. (Kimmo); Elliott, R. J. (Roger J.), 1928- (Imperial College Press ; Distributed by World Scientific, 2005)
This indispensable book is a compilation of invited talks delivered at the symposium, "Current Topics in Physics" held in Mexico City in June 2003, to celebrate the 75th birthday of Professor Sir Roger Elliott. The contributions have been prepared by research associates, former students, post-doctoral fellows and colleagues of Professor Elliott, many of them leading scientists - as Sir Roger himself - in important research institutes around the world. The book gives a very timely and comprehensive overview of various key areas of modern condensed matter and statistical physics. 19 original contributions are included, grouped in three main areas: disorder and dynamical systems, structures and glasses, electrical and magnetic properties. The contributions are by many of the foremost researchers in the field of condensed matter and statistical physics. In particular, contributions by such prominent scientists as M E Fisher, A A Maradudin, M F Thorpe, M Balkanski, T Fujiwara, and of course Sir Roger Elliott himself make this book a rewarding read.